Teologi Ekonomi Kontekstual Sebagai Respon Terhadap Konsumerisme - Wijaya, Yahya (Jurnal Orientasi Baru, 2007)
Christian theology has been referred as a criticism against consumerism. Yet, the position of some Christian traditions regarding economic life is quite ambivalent. On the one hand, some traditions show their followers the value of a simple lifestyle; on the other hand, some traditions drive them to be pioneers in business and industry, producing goods including luxurious ones which eventually promote extreme consummerism. In Indonesia, consumerism is as vast as in the West, but it is related more to the supply of imported commodities. Therefore, while a theological re-insistment on a simple lifestyle may not be helpful in the West, it is still relevant to the Indonesian context. A contextual economic theology does not only need to be critical ofconsumerism, but should stimulate productivity. The image of a morally responsible consumer interacting with morally responsible producers would be more appealing than that of an ascetic person from the pre-globalized era.